#1

Before you ask, yes I have used the search bar ;P

hopefully someone here can explain it to me... I have to prove statements using proofs..but I'm not understanding it at all.

here is an example the teacher gave us

there was another one... -(-a)=a I had three steps and got it wrong...

Can anyone explain to me how to do these damn things?

btw, i'm in algebra 2

hopefully someone here can explain it to me... I have to prove statements using proofs..but I'm not understanding it at all.

here is an example the teacher gave us

```
-(a-b)=b-a
1. -(a-b) 1. Given
2. -(a+-b) 2. Subtraction Theorem
3. -1(a+-b) 3. Multpl. Prop of -1
4. -a+b 4. Distrubative property
5. b+-a 5. Communiative Property
6. b-a 6. Subtraction theorem
```

there was another one... -(-a)=a I had three steps and got it wrong...

Can anyone explain to me how to do these damn things?

btw, i'm in algebra 2

#2

i think i get it so it would be

1. -(-a)=a

2. +a=a

3. a=a

i think i got it right.

1. -(-a)=a

2. +a=a

3. a=a

i think i got it right.

*Last edited by thefoundationof at Sep 22, 2007,*

#3

i think i get it so it would be

1. -(-a)=a

2. +a=a

3. a=a

i think i got it right.

I had

1. -(-a)

2. -1(-a)

3. a=a

(Pretty much what you had)

and got it wrong

EDIT: i remember her saying it was 6 steps..

#4

why oh why do you need 6 steps to prove that? it's practically a given thing in maths in england.

#5

I have no idea. I really don't. She teaches right out of the book, and book doesn't even explain it..so I am really lost at the moment...(with a test coming up on monday! yay!)

#6

6 steps hmm ok

1.-(-a)=(a)

2.-(-a)-a=a-a

3.-(-a)-a=0

4.-1(-a)-a=0

5.a-a=0

6.0=0

idk im in algebra 1

EDIT: the other a's came from subtracting the a on the right side by both sides.

1.-(-a)=(a)

2.-(-a)-a=a-a

3.-(-a)-a=0

4.-1(-a)-a=0

5.a-a=0

6.0=0

idk im in algebra 1

EDIT: the other a's came from subtracting the a on the right side by both sides.

*Last edited by thefoundationof at Sep 22, 2007,*

#7

a proof cannot end with the line "0=0"

#8

a proof cannot end with the line 0=0.

oh I didn't know that, well, I haven't been taught that yet.

#9

6 steps hmm ok

1.-(-a)=(a)

2.-(-a)-a=a-a

3.-(-a)-a=0

4.-1(-a)-a=0

5.a-a=0

6.0=0

idk im in algebra 1

well...all you'd have to do is add a to the other side.

so 6. would be a=a

but uh...where the hell are you getting those other a's from?

#10

why oh why do you need 6 steps to prove that? it's practically a given thing in maths in england.

Basically, you should be able to prove everything you do with the basic axioms.

But I don't really see what these 6 steps in proving -(-a) = a. This is how one of my math professor proved it:

" Thesis: -(-a) = a

The thesis means that the complement of -a, which is -(-a), equals a. This is true, because:

(-a) + a = a + (-a) = 0."

#11

TS are you by any chance a freshman in geometry honors?

#12

Sophmore in Advanced Algebra

#13

-(-a) = a

-1(-1 x a) = a

(-1 x -1)a = a

a = a

some bollocks like that

-1(-1 x a) = a

(-1 x -1)a = a

a = a

some bollocks like that

#14

-(-a) = -(-a) + 0 = -(-a) + (a + (-a)) = (a + (-a)) -(-a) = a + ((-a) - (-a)) = a.